Preferensi Kenyamanan Pengunjung di Kebun Raya Bogor selama Adaptasi Kebiasaan Baru Berbasis Big Data - Paramitadevi, Yudith Vega; Jannah, Nurul; Mindara, Gema Parasti (ARSITEKTURA, 2021)
Urban communities need urban forests in improving the quality of mental  and physical health during the New Normal. If ecotourism or urban forest is a top priority in implementing the New Normal, managers must determine designs, and make procedures related to the applicable COVID-19 protocol. The research objective was to measure the comfort level of visitors before and during the pandemic using big data, then compile comfort design recommendations according to visitor preferences during the pandemic based on survey methods. Social media Twitter and Google Map Review mentioning the Bogor Botanical Garden were collected a year before and six months during the pandemic. Analysis of text mining is carried out in order to obtain sentiment and initial perceptions about the Bogor Botanical Garden. Initial perceptions of visitors were used to construct the survey questionnaire. Furthermore, quantitative survey methods were used to analyze visitor activity and comfort. Visitor comfort is limited to abiotic factors, namely accessibility, and facilities. Sentiment analysis shows pre-pandemic conditions had 48.26% more positive word frequency than during the pandemic for Twitter, but 23.29% less than during the pandemic for Google Map Review. Twitter are more sensitive to the current situation than Google Map Review. Positive perceptions of comfort include compliance management of KRB under the COVID-19 protocol (11.7%), better management (10.8%), well-maintained facilities and infrastructure (7.2%), and maintained hygiene (7.2%). Comfort design recommendations based on respondents' preferences for comfort (14.4%) include increasing the number of toilets, the number of rest areas, ramps for the elderly, areas and attractions to attract children, parks with new themes, and sustainability elements.